(untitled) (Bangladesh Journal of Neuroscience, 2014)
Background: A sample of 60 subjects from population based study participated in a study on carotid color duplex ultrasonography that aimed to assess the relations of coagulation factors to stroke and carotid atherosclerosis. The association between severity of carotid atherosclerosis and high factor viii activity in ischemic stroke is still not clear. Objective: The present study was conducted to find out the association between carotid atherosclerosis and high factor viii activity in ischemic stroke. Methodology: This was a cross sectional analytical study carried out in the department of neurology,BSMMU during the period of july’2009 to june’2011.A total 60 subjects with ischemic stroke were included in this study and data were collected purposively. Chi square test was done and probability value <0.05 were considered as level of significance and 95% confidence limit were taken. Result: In patients with e”50% carotid stenosis, 7(23.33%) had high factor VIII activity and 23(76.67%) had normal factor VIII activity. In patients with <50% carotid stenosis, 2(6.67%) had high factor VIII activity and 28(93.33%) had normal factor VIII activity. No significant difference (P>0.05%) was found between the high factor VIII activity and normal factor VIII activity related to severity of carotid stenosis. Conclusion: The roles of hypertension, hypercholesterolemia, and hypertriglyceridemia have been implicated in the pathogenesis of the carotid atherosclerosis but in the present study did not find any association between the severity of the carotid atherosclerosis with high factor viii activity in ischemic stroke. Bangladesh Journal of Neuroscience 2014; Vol. 30 (1): 1-10